2012
DOI: 10.1017/s0317167100013500
|View full text |Cite
|
Sign up to set email alerts
|

MS Patients Report Excellent Compliance with Oral Prednisone for Acute Relapses

Abstract: Background:Multiple Sclerosis is characterized by relapses separated by periods of relative quiescence. High dose intravenous corticosteroid pulses for three to five days is the current standard for the treatment of acute relapses, but recent evidence supports the use of equivalent doses of oral therapy as an alternative. The highest single dose preparation of oral prednisone is a 50mg tablet, requiring patients to take 25 tablets a day. Questions regarding compliance with this oral regimen have been raised.Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…12 Considerable variability between specialists in the prescription of this treatment has been observed in clinical practice. 13,14 Patients tend to prefer oral administration over intravenous therapy, [15][16][17][18] because it interferes less with family and social life, is more convenient, and avoids the contact with needles. In keeping with the hypothesis investigated by other authors that oral methylprednisolone (oMP) is not inferior clinically or radiologically to intravenous methylprednisolone (ivMP), and that it is equally well tolerated and safe, [17][18][19] we conducted the present clinical trial for the treatment of MS relapse with the aim of providing evidence that would tilt the scale toward oral administration of steroids to spare patients from more invasive, less convenient, and more costly medical practice.…”
Section: A Randomized Clinical Trial Of Oral Versus Intravenous Methylprednisolone For Relapse Of Msmentioning
confidence: 99%
“…12 Considerable variability between specialists in the prescription of this treatment has been observed in clinical practice. 13,14 Patients tend to prefer oral administration over intravenous therapy, [15][16][17][18] because it interferes less with family and social life, is more convenient, and avoids the contact with needles. In keeping with the hypothesis investigated by other authors that oral methylprednisolone (oMP) is not inferior clinically or radiologically to intravenous methylprednisolone (ivMP), and that it is equally well tolerated and safe, [17][18][19] we conducted the present clinical trial for the treatment of MS relapse with the aim of providing evidence that would tilt the scale toward oral administration of steroids to spare patients from more invasive, less convenient, and more costly medical practice.…”
Section: A Randomized Clinical Trial Of Oral Versus Intravenous Methylprednisolone For Relapse Of Msmentioning
confidence: 99%
“…However, oral medication may be more convenient, minimizing travel to an infusion center, especially for those residing in rural locations. In addition, our previous study showed that oral administration is preferred by persons with MS . The use of oral administration is also more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Participants randomized to the oral group were provided 75 tablets of 50 mg of prednisone (25 tablets daily) to consume at home. Compliance with this oral regimen has been previously shown to be very high (compliance rate, 98%) . No taper was used after the 3-day treatment because previous research indicates tapering has no effect on short- or long-term outcomes …”
Section: Methodsmentioning
confidence: 99%
“…Recovery was equal with or without subsequent oral corticosteroid tapering. [33] (2) Plasma exchange: Patients who experience fulminant attacks that do not respond to glucocorticoids may benefit from 5 to 7 exchanges:40 to 60 mL/kg each exchange given every other day for 14 days. However, the price is considerable, and there is not enough solid proof of its effectiveness.…”
Section: Treatment Of Acute Relapsesmentioning
confidence: 99%